2014
DOI: 10.5372/1905-7415.0803.295
|View full text |Cite
|
Sign up to set email alerts
|

Original article. Biting behavior of Malaysian mosquitoes, Aedes albopictus Skuse, Armigeres kesseli Ramalingam, Culex quinquefasciatus Say, and Culex vishnui Theobald obtained from urban residential areas in Kuala Lumpur

Abstract: Background: There are several species of mosquitoes that readily attack people, and some are capable of transmitting microbial organisms that cause human diseases including dengue, malaria, and Japanese encephalitis. The mosquitoes of major concern in Malaysia belong to the genera Culex, Aedes, and Armigeres. Objective: To study the host-seeking behavior of four Malaysian mosquitoes commonly found in urban residential areas in Kuala Lumpur. Methods: The host-seeking behavior of Aedes albopictus, Armigeres kess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 11 publications
7
18
0
1
Order By: Relevance
“…However, the result also shows a distinct number of Ae. albopictus collected from 7:30 to 8:30 a.m. and throughout morning hours, supporting previous studies that found their biting behavior peaked during dawn and dusk in a 24-h cycle [ 10 , 22 ]. It is generally considered that Ae.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the result also shows a distinct number of Ae. albopictus collected from 7:30 to 8:30 a.m. and throughout morning hours, supporting previous studies that found their biting behavior peaked during dawn and dusk in a 24-h cycle [ 10 , 22 ]. It is generally considered that Ae.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the nocturnal behavior of mosquitoes, most research on biting activity has been conducted between sunset and sunrise. However, a study conducted by Chen et al [ 10 ] on the biting activity of Ae. albopictus in urban areas reported the highest biting peak as occurring between 6:00 and 9:00 a.m. and between 3:00 and 8:00 p.m. Mangrove forests represent an important refuge habitat for adult mosquitoes due to high humidity and shaded canopy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, current studies demonstrate considerable variation in Ae . albopictus density and human biting within a city and across land-use types [ 21 , 39 , 56 ]. More field data and behavioral evaluation are needed to refine model assumptions and parameters regarding when and where mosquito density and percent human feeding is likely to facilitate onward human transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Aedes mosquito is a diurnal feeder with peak biting periods in the early morning and in the evening [ 1 ], but surveys have shown that the biting activity of Aedes albopictus varies from place to place. For example, in Malaysia the activity peak is observed between 0600–0900 and 1500–2000 [ 41 ], and in Macau (near Guangzhou), between 0600–0800 and 1800–2000 [ 42 ], but in India, it shifts to 2230–2300 and 2030–2100 [ 43 ]. In our study, we assume that the biting rate during daytime and nighttime is the same, but has different values in different districts.…”
Section: Methodsmentioning
confidence: 99%